AB0011 The Genetics of Behcet's Disease: a Novel Variation of Erap1 Gene in an Italian Cohort. (9th June 2015) - Padula, M.C.; Mecca, M.; D'Angelo, S.; Leccese, P.; Gilio, M.; Olivieri, I.; Martelli, G.
Abstract : Background: The genetics of Behcet's disease: a novel variation of ERAP1 gene in an Italian cohort Objectives: The objective of the present study was to evaluate the association of ERAP1 gene with BD in an Italian cohort by investigating not only tagSNPs but all gene regions searching for additional variations probably related to the BD phenotype. Methods: Genomic DNA was isolated from 21 BD patients whole blood by using a commercial kit. The patient cohort was recruited from the Rheumatology Departments of Lucania (San Carlo Hospital - Potenza and Madonna delle Grazie Hospital - Matera, Italy) and was formed by 11 males and 10 females with a mean age of 45 years. The purity of DNA was determined by means of NanoDrop spectrophotometer. Specific PCR primers was designed on the basis of ERAP1 NCBI RefSeq (NG_027839.1) in order to cover all 21 gene exons and used for in vitro amplification. PCR products were directly sequenced and bioinformatically analysed. The functional impact of the gene variants was evaluated by querying Polyphen 2 software. Results: Mutation analysis of the entire ERAP1 gene underlined a novel variation within exon 7. It was found in 3/21 patients (14%) and consists in the substitution p.Phe360Cys (NG_027839.1:g.25637T>G; NP_057526.3:p.Phe360Cys). Interestingly the novel mutation was identified in association with three known tagSNPs (p.Met349val, p.Lys528Arg and p.Gln730Glu) and was predicted to have damaging effects on protein (maximum score of pathogenicity). Conclusions: ERAP1 was recently considered a BD susceptibility gene. Five tagSNPs was previously reported to be related to BD phenotype. We firstly analysed an Italian BD patient cohort. In addition, we firstly investigated the entire ERAP1 gene, because searching only for common variants by GWAS allows to identify a fraction of the entire genetic burden of disease. In this study, three known gene variations were found in three patients belonging to our cohort, in association with our novel variation. This aspect suggests a significant role of the novel substitution in the pathogenesis of BD. The identification of novel functional variants of entire ERAP1 gene may lead to better stratification of BD patients by providing a diagnostic tool and a potential therapeutic target. References: Gul A. Current Opinion in Rheumatology 2014; 26:56-63. Conde-Jaldòn M, Montes-Cano MA, Garcìa-Lozano JR, Ortiz-Fernández L, Ortego-Centeno N, González-Leόn R, Espinosa G, Graña-Gil G, Sánchez-Bursόn J, González-Gay MA, Barnosi-Marín AC, Solans R, Fanlo P, Carballeira MR, Camps T, Castañeda S, Martín J, González-Escribano MA. 2014. PlosOne; 9: 1-6. Kirino Y1, Bertsias G, Ishigatsubo Y, Mizuki N, Tugal-Tutkun I, Seyahi E, Ozyazgan Y, Sacli FS, Erer B, Inoko H, Emrence Z, Cakar A, Abaci N, Ustek D, Satorius C, Ueda A, Takeno M, Kim Y, Wood GM, Ombrello MJ, Meguro A, Gül A, Remmers EF, Kastner DL. Nat Genet. 2013; 45(2): 202-207. Carmona FD1, Martín J, González-Gay MA. Curr Opin Rheumatol. 2015; 27(1): 10-17. Reeves E, Elliott T, James E, Edwards CJ. 2014; 60(2-3): 257-69. O'Rielly DD, Rahman P. Best Pract Res Clin Rheumatol. 2014; 28(5): 673-685. Disclosure of Interest: None declared